2020
DOI: 10.1109/tnse.2020.3007472
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Optimal State Consensus for Multiple Circuit Systems With Disturbance Rejection

Abstract: This paper investigates the distributed optimal state consensus problem for an electronic system with a group of circuit units. The dynamics of each unit is modeled by a Chua's circuit in the presence of disturbance generated by an external system. By means of the internal model approach and feedback control, a compensator-based continuous-time algorithm is proposed to minimize the sum of all cost functions associated with each individual unit in a cooperative manner. Supported by convex analysis, graph theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…During the last decade, cooperation control of MASs has found substantial success in a variety of applications, such as consensus [1][2][3], tracking control [4][5][6], formation control [7,8], containment 2 NON-FRAGILE CONTAINMENT CONTROL control [9], cooperative output regulation [10] and optimization [11]. Consensus problem, as a fundamental and non-negligible research topic of MASs, requires that all agents achieve an agreement on a common state, depending on the designed consensus protocols using only relative measurements among neighboring agents.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, cooperation control of MASs has found substantial success in a variety of applications, such as consensus [1][2][3], tracking control [4][5][6], formation control [7,8], containment 2 NON-FRAGILE CONTAINMENT CONTROL control [9], cooperative output regulation [10] and optimization [11]. Consensus problem, as a fundamental and non-negligible research topic of MASs, requires that all agents achieve an agreement on a common state, depending on the designed consensus protocols using only relative measurements among neighboring agents.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference 26, the distributed optimal consensus problem for minimum‐phase uncertain nonlinear systems with unity‐relative degree and disturbances was considered based on nominal and nonfragile cases. Further, In Reference 27, the distributed optimal state consensus problem for an electronic system, compared with the centralized algorithms, the proposed protocol possesses remarkable superiority in improving the scalability and reliability of multiple circuit systems. In Reference 28, a novel adaptive control scheme is developed for active suspension systems to solve the time‐varying.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is revealed that observer gains may show insignificant drifts because sensor equipment gets aging since they are produced offline. More outcomes on nonfragile cases and states uncertainty cases for nonlinear systems can be found in References 47‐54. However, there are some limitations in present works: (a) The observer gains are obtained by solving some linear matrix inequalities (LMIs).…”
Section: Introductionmentioning
confidence: 99%